Characterization of Severe Arterial Phase Respiratory Motion Artifact on Gadoxetate Disodium-Enhanced MRI – Assessment of Interrater Agreement and Reliability - Ringe, Kristina Imeen; Luetkens, Julian A.; Fimmers, Rolf; Hammerstingl, Renate Maria; Layer, Günter; Maurer, Martin H.; Nähle, Claas Philip; Michalik, Sabine; Reimer, Peter; Schraml, Christina; Schreyer, Andreas G.; Stumpp, Patrick; Vogl, Thomas J.; Wacker, Frank K.; Willinek, Winfried; Kukuk, Guido Mattias (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose To assess the interrater agreement and reliability of experienced abdominal radiologists in the characterization and grading of arterial phase gadoxetate disodium-related respiratory motion artifact on liver MRI.Materials and Methods This prospective multicenter study was initiated by the working group for abdominal imaging within the German Roentgen Society (DRG), and approved by the local IRB of each participating center. 11 board-certified radiologists independently reviewed 40 gadoxetate disodium-enhanced liver MRI datasets. Motion artifacts in the arterial phase were assessed on a 5-point scale. Interrater agreement and reliability were calculated using the intraclass correlation coefficient (ICC) and Kendall coefficient of concordance (W), with p < 0.05 deemed significant.Results The ICC for interrater agreement and reliability were 0.983 (CI 0.973 – 0.990) and 0.985 (CI 0.978 – 0.991), respectively (both p < 0.0001), indicating excellent agreement and reliability. Kendall’s W for interrater agreement was 0.865. A severe motion artifact, defined as a mean motion score ≥ 4 in the arterial phase was observed in 12 patients. In these specific cases, a motion score ≥ 4 was assigned by all readers in 75 % (n = 9/12 cases).Conclusion Differentiation and grading of arterial phase respiratory motion artifact is possible with a high level of inter-/intrarater agreement and interrater reliability, which is crucial for assessing the incidence of this phenomenon in larger multicenter studies.Key Points Citation Format
Keywords: gadoxetate disodium; Gd-EOB-DTPA; motion artifact; respiratory; interrater agreement; interrater reliability